Secreción de hormonas tiroideas - Pisarev, Mario Alberto; Altschuler, Noé; Kramar de Valmaggia, Emilia; Balatti, J. J. (1972)
Fil: Pisarev, Mario Alberto. Comisión Nacional de Energía Atómica; Argentina